Loggerhead Turtles (Caretta caretta) in the California Current: Abundance, Distribution, and Anomalous Warming of the North Pacific - Eguchi, Tomoharu; McClatchie, Sam; Wilson, Cara; Benson, Scott R.; LeRoux, Robin A.; Seminoff, Jeffrey A. (Frontiers in Marine Science, 2018)
Environmental variability affects distributions of marine predators in time and space. With expected changes in the ocean climate, understanding the relationship between species distributions and the environment is essential for developing successful management regulations. Here we provide information on an ephemeral but important habitat for North Pacific loggerhead turtles (Caretta caretta) at the northeastern edge of their range. North Pacific loggerhead turtles nest on Japanese beaches and juveniles disperse throughout the North Pacific; some remain in the high seas of the central North Pacific whereas others transition to the eastern Pacific and forage near Baja California, Mexico. Loggerheads have also been reported along the U.S. west coast, with the majority of sightings off southern California. Here we describe their demography and distribution in the area, based on two aerial surveys (2011, 2015), at-sea sightings, and stranding records. Our aerial survey during fall 2015 determined density, abundance, and distribution of loggerheads in the area, when anomalous warming of the North Pacific and El Niño conditions co-occurred. Using line-transect analysis, we estimated ca. 15,000 loggerheads at the sea surface (CV=21%) and more than 70,000 loggerheads when accounting for those that were submerged and not available for detection. Our survey during fall 2011 resulted in no loggerhead sightings, demonstrating a high variability of loggerhead density in the region. We encourage further research on loggerheads in the area to determine the mechanisms that promote their occurrence. These studies should include regular surveys throughout their foraging areas along the west coast of the North America as well as assessments of prey availability and local oceanographic conditions.